Modelling and simulation of lanthanum (La) and neodymium (Nd) leaching from monazite ore using METSTM - Yahya, Fatin Nasuha; Wan Ibrahim, W. H.; Abdul Rasid, Ruwaida; Hisyam, Anwaruddin; Mat Suli, Liyana Nadirah (IOP Publishing, 2020)
Digestion and leaching are known as part of the main processing pre-treatment method in the extraction of rare earth elements (REEs). This work aims to carry out the sensitivity analysis of the liquid–solid (L/S) ratio, the type of acids as well as the number of reactors for the recovery of REEs, namely lanthanum (La) and neodymium (Nd) from monazite concentrate through the leaching process. A model was developed and simulated by using METSIM, a software for modelling metallurgical processes. The process was modelled as a two-step process; the first is the digestion, followed by the leaching process to produce monazite leachate. The results show that the optimum L/S ratio was 8:1 to recover the highest amount of REEs, with HCl was found to perform better as a solvent for the recovery of REEs compared to H2SO4. In addition, the optimum recovery of REEs was achieved by using three reactors, which is in the range of 70-95%.